Studies on the Controlled Release of Drugs from Magnetic Nanobiocomposites - Thomas Heinze; Robert Müller; Mengbo Zhou; Martin Rabel; Paul Warncke; Dagmar Fischer (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2019)
Magnetic nanocomposites are a class of smart materials that have attracted recent interest as drug delivery systems or as medical implants. In this study, meltable nanobiocomposites (NBC) composed of biocompatible dextran fatty acid ester and magnetic nanoparticles (MNPs) melting close to human body temperature were prepared and loaded with Rhodamine B (RhB) or green fluorescent protein (GFP) as model drugs to evaluate their potential use as drug delivery system. The release of the model drugs from the magnetic NBC investigated under the influence of a high frequent alternating magnetic field (AMF, 20 kA/m at 400 kHz) showed that on-demand release is realized applying the external AMF. The NBC showed a long-term stability (28 d) of the incorporated iron oxide particles after incubation in artificial body fluids. This work reveals the potential of the NBC as a drug carrier.